2015
DOI: 10.1007/s11127-015-0248-9
|View full text |Cite
|
Sign up to set email alerts
|

The political economics of redistribution, inequality and tax avoidance

Abstract: A benchmark result in the political economy of taxation is that the degree of redistribution is positively linked to income inequality. However, empirical evidence supporting such a relationship turns out to be mixed. This paper shows how these different empirical reactions can be rationalized within a simple model of tax avoidance and costly tax enforcement. By focussing on structure induced equilibria in which taxpayers vote over the size of the income tax and the level of tax enforcement, we show that highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…However, one cannot examine the impact of redistribution through taxes on income inequality without considering tax avoidance and the high cost involved in ensuring tax compliance. Bethencourt and Kunze (2015) confirmed that when governments increase taxes to combat the increasing inequality, more people will find ways to evade tax through reducing their tax liabilities and, hence, less revenue will be available to redistribute. It is, therefore, imperative for governments to establish an equitable tax system which is also not costly to implement.…”
Section: Ijdi 223mentioning
confidence: 96%
“…However, one cannot examine the impact of redistribution through taxes on income inequality without considering tax avoidance and the high cost involved in ensuring tax compliance. Bethencourt and Kunze (2015) confirmed that when governments increase taxes to combat the increasing inequality, more people will find ways to evade tax through reducing their tax liabilities and, hence, less revenue will be available to redistribute. It is, therefore, imperative for governments to establish an equitable tax system which is also not costly to implement.…”
Section: Ijdi 223mentioning
confidence: 96%
“…Most of the papers try to fill the gap between the Meltzer–Richard hypothesis and the empirical evidence. Bethencourt and Kunze () used the concept of the structure‐induced equilibrium (Shepsle, ) to obtain the income tax and level of tax enforcement chosen simultaneously by majority vote. The authors found that higher income inequality may imply lower income redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative characterization of the aforementioned median voter theorem is given in Gans and Smart (1996) using the single-crossing property on preference profiles. Traxler (2009Traxler ( , 2012, Besfamille et al (2013), and Bethencourt and Kunze (2015) apply the median voter theorem to the tax enforcement problem to determine the enforcement level. In the context of enforcement of illegal immigration, Garca (2006), and Facchini and Testa (2014) use the median voter theorem to determine the enforcement level.…”
Section: Introductionmentioning
confidence: 99%